Economic competitiveness of compact steam methane reforming technology for on-site hydrogen supply: A Foshan case study. (5th September 2022) - Zhang, Chao; Song, Pengfei; Sui, Yiyan; Hou, Jianguo; Wang, Xiulin
Abstract: On-site hydrogen production through steam-methane reforming (SMR) from city gas or natural gas is believed to be a cost-effective way for hydrogen-based infrastructure due to high cost of hydrogen transportation. In recent years, there have been a lot of on-site hydrogen fueling stations under design or construction in China. This study introduces current developments and technology prospects of skid-mounted SMR hydrogen generator. Also, technical solutions and economic analysis are discussed based on China's first on-site hydrogen fueling station project in Foshan. The cost of hydrogen product from skid-mounted SMR hydrogen generator is about 23 CNY/kg with 3.24 CNY/Nm 3 natural gas. If hydrogen price is 60 CNY/kg, IRR of on-site hydrogen fueling station project reaches to 10.8%. While natural gas price fall to 2.3 CNY/Nm 3, the hydrogen cost can be reduced to 18 CNY/kg, and IRR can be raised to 13.1%. The conclusion is that skid-mounted SMR technology has matured and is developing towards more compact and intelligent design, and will be a promising way for hydrogen fueling infrastructures in near future. Highlights: Development status and future expectation of hydrogen refueling stations and fuel cell vehicles in China. On-site hydrogen generator can significantly reduce the cost of hydrogen. Technical composition and global development status of On-site hydrogen generator form natural gas. China's first on-site natural gas to hydrogen refueling station in Foshan.